Developing and Implementing an Airline Stores and Purchases Accounting System: A Case Study of PIA - Syed Sartaj Qasim (Institute of Business Management, 2018)
This case study explains the process of developing and implementing a new microcomputer based accounting system for the Stores and Purchases department of PIA. After briefly highlighting some difficulties which were experienced under the existing manual accounting system, the study continues to chart the various steps which were taken to analyse and map different processes and explains how various modules were developed and tested through parallel runs and ultimately resulted in full cutover to the new computerized accounting system. The role of involving all the existing staff and using their expertise and inputs in the development of the new computerized accounting system has been highlighted as a major factor in its successful implementation.